Notes on three Proto-Slavic borrowings - Derksen, Rick (Vilnius University Open Series, 2021)
The Proto-Slavic etyma *dъska, *misa, and *bļudo (*bļudъ), which are semantically related, are generally regarded as borrowings, but there is no consensus on the exact origins of these nouns. Following surveys of the Old Church Slavic and Gothic evidence as well as of the distribution of the etyma in Slavic, the article discusses the merits and drawbacks of the various existing views. It is argued that *dъska, *misa are best regarded as borrowings from Vulgar Latin or Early Romance, while *bļudo (*bļudъ) must have been borrowed from Germanic, but not from Gothic or West Germanic.
Keywords: language contact; borrowing; Proto-Slavic; Old Church Slavic; Gothic; Germanic; Latin